Ammonium-nitrogen Supply Induces Growth, Physiological and Secondary Metabolites Changes in Centella asiatica L. Urban - Hoang, H.L.; Tran, H.; Do, T.; Rehman, H.; Kawarazuka, Nozomi; Tran, B.; Truong, D. (Agricultural Research Communication Center, 2022)
Background: Centella [Centella asiatica (L.) Urban], as a herb, is well known for its nutritional and pharmaceutical value. Nitrogen fertilizer plays a significant role in yield and quality of the herb. The present study was aimed to evaluate the effect of mineral nitrogen on the centella plant yield, total chlorophyll, total flavonoid content, antioxidant activities and C/N ratio.